PENGARUH DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI MTS MA’ARIF NU 04 DESA KLADI KECAMATAN CERMEE BONDOWOSO - Ziyadatul Widad; Fathor Rakhman; Lusi Endang Sri Darmawati (At- Ta'lim : Jurnal Pendidikan, 2022)
This research was conducted with the aim of improving students' learning discipline. Learning is an important process for changing human behavior and includes everything that is thought and done. To measure whether someone has learned, it is necessary to compare the behavior before and after experiencing learning. Discipline is someone who learns to voluntarily follow the leader. Parents and teachers are leaders and children are students towards a better and more useful life. Using a quantitative approach with ex post facto research involving 60 students in even semesters at MTs Ma'arif Nu 04 Kladi Village, Cermee District, Bondowoso Regency. The results of this study are divided into three, namely, (1.) There is an influence of learning discipline (X) on student learning achievement (Y) at MTs Ma'arif nu 04 Kladi Village, Cermee Subdistrict, Bondowoso Regency for the 2020/2021 academic year. From the research results obtained using the regression line analysis of variance formula yielding Ry (1,2) of 0.537 Which when consulted with the r table with N as many as 60 respondents and a significant level of 5% obtained 0.254 the calculation is intended to prove the major working hypothesis by using the test significant.